Dona de casa e da própria vida? Leituras sobre o trabalho feminino na publicidade por mulheres da nova classe trabalhadora - Oliveira-Cruz, Milena Carvalho Bezerra Freire de (2016)
This thesis aims to understand the ways in which the representations of female labour in advertising are interpreted by women from the new working class as well as the ways in which such representations collaborate with their class and gender habitus. In the field of Communications, it is based on audience research within Cultural Studies, thus drawing on the lived experiences and the everyday life of subjects in order to observe the conformation of their identities in reference to the established relation between communication and culture. This is an important study given both the current gaps within Communications in terms of the articulation of the concepts of class and gender as analytical categories as well as the necessary contribution to the field of advertising reception. The theoretical and analytical assemblage of the topic is built upon Pierre Bordieu s articulation of social theory (especially his concepts of class and gender habitus), Jesús Martín-Barbero s take on mediations, and Néstor García Canclini s concept of media consumption. I empirically mapped out the studied context drawing on a quantitative survey with 396 women in the city of Santa Maria (RS, Brazil). In qualitative terms, I worked with a group of seven women from the new working class, whose ages ranged from 30 to 45 years-old, who lived in the aforementioned city as well. The group s class and gender identity was investigated through data collected throughout one year of participant observation, in-depth interviews, and assisted distribution of adverts selected by the informants, relating and comparing the perception they have of the representations of female labour in advertising to their own experiences and self-representation. Results point to a critical reading when it comes to comprehending the formats, spaces, and logic of the messages of advertising, highlighted by their rituality. In reference to the representations of class and gender, advertising messages sustain the double subordination to which women from the working class are submitted. Even though the group of women herein studied recognise the appreciation of the lifestyle of the working class, the idealisation of work, and the male domination, there is a tendency, within these women, to appropriate values present in advertising by means of the naturalisation of the space and the role which are socially assigned to them as working class women.